Relationship between hepatitis C virus antibody and viral load in HIV-infected individuals: a hospital-based study in Yunnan province - Lijuan KANG; Junyi LIU; Yantao ZHU; Mi ZHANG; Nian ZHANG; Qi XIE; Shifang LIU; Jiantao YANG; Xiao LI; Quanying HE; Jiali WANG (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo understand the correlation between hepatitis C virus (HCV) antibodies and HCV RNA viral load in HIV co-infected individuals and to provide a basis for predicting HCV RNA based on HCV antibody detection. MethodsThe blood samples and relevant data were collected from 979 HIV-infected individuals with HCV antibody detection at the Yunnan Provincial Infectious Disease Hospital from November 2022 to March 2023. HCV antibodies were detected by enzyme-linked immunosorbent assay (ELISA), and HCV RNA was measured by real-time reverse transcription-PCR (qRT-PCR). T-test and chi-squared test were used for data analysis. ResultsAmong all participants, 17.9% (n = 176) were HCV antibody positive, and the positive rates were 17.1% (n = 110) and 19.6% (n = 66) for male and female participants, respectively. The rate of HCV antibody positivity was associated with age (χ2 = 107.662, P < 0.001), with the highest rate of 29.6% in participants aged 41 - 60 years and the lowest rate of 0% in participants younger than 20 years. Among participants who were HCV antibody positive, the HCV RNA positivity rate was 46.6%, with positive rates of 50.0% and 40.9% in male and female participants, respectively, and the positive rate was not related to age (P > 0.05). Spearman rank correlation analysis showed a positive correlation between HCV RNA positivity and HCV antibody levels (r = 0.237, P < 0.05). Receiver operating characteristic (ROC) curve analysis showed that an HCV antibody level ≥ 16.78 (signal to cutoff ratio, S/CO) indicated HCV RNA positivity. ConclusionThe rate of HCV antibody positivity was high in the HIV-infected population and positively correlated with HCV RNA levels, with an S/CO value of 16.78 being an optimal threshold for predicting HCV RNA positivity, which could be used in the diagnosis and management of patients co-infected with HIV and HCV.